Asketisme dalam Ajaran Yoga - I Wayan Nerta (UHN IGB Sugriwa Denpasar, 2015)
Acceleration of science and technology enhances the positive sides of men’s life. However, as the social problems remain, peace is just needed. The Hindu Yoga can help people to experience spiritual freedom therefore gain peaceful life. It teaches discipline and strength to the mind, body, and soul.